Is There Any Point in a Corticosteroid Treatment of Intermittent Asthma? - Ivana Stankovic; Tatjana Pejcic; Branislava Milenkovic; Dragana Jovanovic; Milan Rancic (The Scientific World Journal)
International guidelines advocate the early introduction of inhaled corticosteroids (ICS) in all types of persistent asthma. Our study was undertaken to assess the effects of ICS on bronchial hyperresponsiveness (BHR) as a hallmark of inflammation, and to assess the symptoms, the use of rescue medications, and the parameters of lung function in patients with mild intermittent asthma. The patients with intermittent asthma (n = 85) were randomly allocated to a treatment with ICS, beclomethasone dipropionate 250 μg/day and short-acting β2 agonists salbutamol as needed (Group A, n = 45) or to a treatment with only short-acting β2 agonists as needed (Group B, n = 40) during the 6-month treatment period. At the end of the study, in Group A, we found a statistically significant decrease of BHR (PD20 0.98 vs. 2.07) (p < 0.001), diurnal peak expiratory flow (PEF) variability (17.9 vs. 13.8) (p < 0.001), symptom scores (0.63 vs. 0.30) (p < 0.001), and used rescue medication (p < 0.001), while the parameters of lung function remained unchanged except for forced expiratory volume in 1 sec (FEV1), which had a statistically significant increase (3.58 vs. 3.66) (p < 0.001). In Group B, there was a statistically significant decrease of lung function parameters FEV1 (3.80 vs. 3.71) (p < 0.001), forced vital capacity (FVC) (4.43 vs. 4.37) (p < 0.001), FEV1/FVC (88.2 vs. 85.3) (p < 0.05), PEF (8.05 vs. 7.51) (p < 0.01), PEF variability (17.85 vs. 18.33) (p < 0.001), increased BHR (PD20 1.04 vs. 0.62) (p < 0.05), and symptom scores (0.46 vs. 0.62) (p < 0.01), as well as the use of rescue medication during the day (p < 0.001). Early introduction of low doses of ICS may be more beneficial than β2 agonists alone in patients with intermittent asthma.